2000
DOI: 10.1021/bi992452y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Peptide Deformylase Inhibitors

Abstract: Peptide deformylase catalyzes the removal of the N-terminal formyl group from newly synthesized polypeptides in eubacteria. Its essential character in bacterial cells makes it an attractive target for antibacterial drug design. In this work, we have rationally designed and synthesized a series of peptide thiols that act as potent, reversible inhibitors of purified recombinant peptide deformylase from Escherichia coli and Bacillus subtilis. The most potent inhibitor has a K(I) value of 11 nM toward the B. subti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…The urea hydroxamates appear to be bacteriostatic against S. aureus, as was observed previously for other PDF inhibitors against both S. aureus and E. coli (4,13,34). Huntington et al (25) reported the lysis of Bacillus subtilis by a peptide thiol PDF inhibitor, although the compound appeared to be bacteriostatic when tested with log-phase organisms. In contrast to the situation with S. aureus, VRC4232 and VRC4307 both had a killing effect on S. pneumoniae and H. influenzae, two pathogens that cause upper respiratory tract infections.…”
Section: Discussionsupporting
confidence: 58%
“…The urea hydroxamates appear to be bacteriostatic against S. aureus, as was observed previously for other PDF inhibitors against both S. aureus and E. coli (4,13,34). Huntington et al (25) reported the lysis of Bacillus subtilis by a peptide thiol PDF inhibitor, although the compound appeared to be bacteriostatic when tested with log-phase organisms. In contrast to the situation with S. aureus, VRC4232 and VRC4307 both had a killing effect on S. pneumoniae and H. influenzae, two pathogens that cause upper respiratory tract infections.…”
Section: Discussionsupporting
confidence: 58%
“…Although bacteriostatic action has also been described for actinonin (11), this may not be a general characteristic of PDF inhibitors, as a series of peptide thiols described recently (15) show bactericidal activity. However, this was only convincingly demonstrated in Bacillus subtilis, which may be particularly susceptible to this class of compounds.…”
Section: Discussionmentioning
confidence: 97%
“…Although Huntington et al reported that a series of peptide thiols were potent PDF inhibitors with whole-cell activity (12), the majority of PDF inhibitors reported to have significant antibacterial activity contain either a hydroxamate or reverse hydroxamate as the metal chelator (31). In fact, in a recent study for which compounds of the same P 1 Ј-P 3 Ј peptidomimetic but with different metal binding groups were prepared, only hydroxamate-and N-formyl hydroxylamine-containing compounds showed antibacterial activity (12a, 30).…”
Section: Discussionmentioning
confidence: 99%